Who cares what it means? Practical reasons for using the word resilience with critical infrastructure operators. (July 2020) - Petersen, L.; Lange, D.; Theocharidou, M.
Highlights: Critical infrastructure operators use a myriad of resilience definitions. A common definition of resilience is not required by them to operationalize it. Resilience is seen to include risk management. Resilience is seen to also include recovery issues, organizational aspects and unforeseen events. This confirms current literature on resilience engineering from an end-use perspective. Abstract: Resilience: a highly debated term, with what seems to be an endless amount of slightly varied definitions depending on the sector, domain, or researcher who is addressing the topic, mainly boils down to rebounding after a crisis. For critical infrastructure (CI), the EU-funded H2020 IMPROVER project used the following definition: "the ability of a CI system exposed to hazards to resist, absorb, accommodate to and recover from the effects of a hazard in a timely and efficient manner, for the preservation and restoration of essential societal services." This was the starting point for much of the work done within that project, however, through six interactive workshops with infrastructure operators organized by the IMPROVER project, what has become apparent is that the definition of resilience isn't what matters; what does matter is the way resilience changes the outlook of operators. This paper presents the results of a critical thematic analysis carried out on the discussions held at these workshops. The findings reflect the practitioners' views on resilience and are in strong agreement with much of the current academic literature, in particular with literature on resilience engineering. One of the main findings is that resilience as a concept is operationalisable and that a lack of a consensus on details of a definition is no obstacle to using the term or striving to operationalise it. Indeed, resilience is an optimistic approach when compared to current risk management practices, allowing operators to be actors in responding to crisis as opposed to simply being subjects exposed to risks. While many aspects of resilience are also found in risk management, the ability to learn how to respond to unexpected events appears to empower operators. Furthermore, the change in perspective from risk to resilience better deals with another change critical infrastructure operators are going through: from protecting assets from hazards to being able to continuously provide a minimum level of essential services to the public.